PEMANFAATAN MEDIA VIDEO ANIMASI PADA PEMBELAJARAN PENDIDIKAN JASMANI DITINJAU DARI HASIL BELAJAR - Anres Gunawan Sianturi, - (2021)
The purpose of this study was to determine how the use of animated video media in physical education learning and the impact of using animated video media on physical education learning in terms of learning outcomes. This research method is a descriptive study with an evaluative approach. The population of this research is SMA Negeri 15 Bandung and the sample of this research is all Physical Education Teachers as main informants and students as supporting informants. Determination of population and sampling is using purposive sampling technique. Based on the results of descriptive analysis, it shows that the use of animated video media in physical education learning is still lacking because only one teacher uses animated video media on physical education learning and the impact of using animated video media on educational learning physical in terms of learning outcomes is good because, if the animated video is made properly it will provide enthusiasm and motivation to students to take part in the learning process.